Comparison of Molar Refraction and Polarizability Constants of substituted Benzo-(4,5-d)-2-Arylimino-7-Aryl/Alkylimino-1,3,6-Thiadiazepines in Different Percentages of Solvents - P. Deohate, Pradip; B. Agrawal, Pratibha; Berad, B.N. (Asian Journal of Chemistry, 2010)
In different percentages of aetone-water and dioxane-water mixtures the densities and refractive indices of benzo-(4,5-d)-2-phenylimino-7-phenylimino- 1,3,6-thiadiazepine (I), benzo( 4,5-d)-2-phenylimino-7-o-tolylimino- 1,3,6-thiadiazepine (II), benzo:(4,5-d)-2-phenylimino-7-m-tolylimino- 1,3,6-thiadiazepine (III), benzo-(4,5-d)-2-phenylimino-7-p-tolylilnino- 1,3;6-thiadiazepine (IV), beazo-(4,5-d)-2-phenylimino-7-o-chlorophenylimino- 1,3,6-thiadiazepine (V), benzo( 4,5-d)-2-phenylimino-7 -p-chlorophenylimino- 1,3,6-thiadiazepine (VI) and benzo-(4,5-d)-2-phenylimino-7- t-butylimino-1,3,6-thiadiazepine (VII) have been measured. From the data the molar refraction and polarizability constants for the compounds have been calculated which have been used to detect the nature of dipoles and to compare the substituted benzo-(4,5-d)-2-arylimino-7-aryl /alkylimino- 1,3,6-thiadiazepines on the basis of presence of different substituents.